ANALISIS DAMPAK COVID-19 TERHADAP RETURN SAHAM DAN ABNORMAL RETURN SAHAM (STUDI EMPIRIS PADA PERUSAHAAN INFRASTRUKTUR TAHUN 2020) - Asri Nadya Putri Yusuf; Maslichah Maslichah; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This research was conducted to analyze how the impact before and after the emergence of covid-19 on stock returns and stock abnormal returns in infrastructure companies. The sample of this research is an infrastructure company that has complete daily stock price data. Sampling in this study used a purposive sampling technique by setting several criteria. This study focused on the 7 days window period before and 7 days of the entry of covid-19, namely on March 2, 2020. Paired sample t-test was used as data analysis for this study. From the research that has been done, it is known that there are differences in stock returns and abnormal stock returns before and during the covid-19 pandemic due to the impact of the covid-19, which is known from the sig (2-tailed) value of 0,045 and 0,046. Where sig (2-tailed) 0,05. Then H1 is accepted and H2 is Accepted. Keywords : Covid-19, Return, Abnormal Return, Infrastructure, Event Period